SMART VILLAGE-BASED ORANGE FARMER DEVELOPMENT SOLUTIONS WITH CYCLE SYSTEM OF PRODUCT INDUSTRIAL ACTIVITIES TOWARD SUSTAINABLE DEVELEOPMENT CITY - Heny Kusdiyanti; Mokhammad Nurruddin Zanky; Andy Prasetyo Wati (Prosiding Conference on Research and Community Services, 2019)
Citrus farmers in Indonesia have different economic capabilities than other farmers, namely they don't know the season so there must be a participation of the community, social organizations, and religion in overcoming the problem of this sweet orange farmer. Not counting this season, has an impact on the poor quality and quantity of sweet orange products produced. In addition, the fluctuations in the price of oranges on the market are also a potential loss of citrus farmers in Poncokusumo Village, Malang Regency. This community service aims to create a product transformation in the form of orange-based sweets to finally succeed in forming industrial activities in the smart village concept through entrepreneurship activities. The implementation of this program is carried out in three stages, namely: (1) planning, (2) implementation, and (3) evaluation. This service was attended by orange farmer groups in Poncokusumo Village consisting of 52 people. This program begins with the delivery of material about the business opportunities for sweets from the sweet orange of Poncokusmo Village, simulations of making sweets, packaging techniques, and simple marketing strategies that can be done by orange farmers. After this service, candy products made from sweet oranges were created from Poncokusumo Village. Not only that, citrus farmers are also taught to make branding of candy products so that they can be marketed and included in the potential Malang souvenir shop. This candy product has the potential to become an industrial activity in the smart village of Poncokusumo Village which will later become the forerunner to the establishment of Poncokusumo UKM to realize the Sustainable Development of Indonesia.